2001
DOI: 10.1128/iai.69.9.5716-5725.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cholera Toxin B Subunit as a Carrier Molecule Promotes Antigen Presentation and Increases CD40 and CD86 Expression on Antigen-Presenting Cells

Abstract: Cholera toxin B subunit (CTB) is an efficient mucosal carrier molecule for the generation of mucosal antibody responses and/or induction of systemic T-cell tolerance to linked antigens. CTB binds with high affinity to GM1 ganglioside cell surface receptors. In this study, we evaluated how conjugation of a peptide or protein antigen to CTB by chemical coupling or genetic fusion influences the T-cell-activating capacity of different antigen-presenting cell (APC) subsets. Using an in vitro system in which antigen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
105
1
3

Year Published

2003
2003
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 143 publications
(117 citation statements)
references
References 59 publications
(61 reference statements)
8
105
1
3
Order By: Relevance
“…treatment with OVA/CTB conjugate is probably largely explained by the effects of the conjugate on gut mucosal APC. Previous studies have shown that conjugation of Ag to CTB, a molecule that binds with high affinity to the GM1 ganglioside receptors present on most cells (30), greatly facilitates Ag uptake and MHC class II-restricted Ag presentation by CD11c ϩ DC as well as other types of APC, such as B cells and macrophages (23). One possibility is that mucosally administered Ag/CTB conjugate preferentially binds to and is taken up by tolerogenic subsets of mucosal DC or other APC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…treatment with OVA/CTB conjugate is probably largely explained by the effects of the conjugate on gut mucosal APC. Previous studies have shown that conjugation of Ag to CTB, a molecule that binds with high affinity to the GM1 ganglioside receptors present on most cells (30), greatly facilitates Ag uptake and MHC class II-restricted Ag presentation by CD11c ϩ DC as well as other types of APC, such as B cells and macrophages (23). One possibility is that mucosally administered Ag/CTB conjugate preferentially binds to and is taken up by tolerogenic subsets of mucosal DC or other APC.…”
Section: Discussionmentioning
confidence: 99%
“…To test the regulatory function of isolated CD4 ϩ T cells or separated CD25 ϩ CD4 ϩ or CD25 Ϫ CD4 ϩ T cells from mice with different treatments, these cells were cocultured in different numbers with 1 ϫ 10 5 DO11.10 T eff cells together with 5 ϫ 10 3 of bone marrow-derived dendritic cells (DC) prepared as described in Ref. 23 and with 1 g/ml OVA 323-339 peptide. These tests were performed using 96-well round-bottom plates (Nunc) for 3 days with [ 3 H]thymidine added during the last 16 h. IL-2 production by cultured cells were assayed in 2-day culture supernatants using the cytokine cytometric bead array method (BD Biosciences).…”
Section: T Cell Proliferation and Cytokine Assaysmentioning
confidence: 99%
“…Molecular mechanism of adjuvant property of rCTB is not understood completely although binding to GM 1 gangliosides is required for rCTB to act as an adjuvant (21). Like other bacterial components, rCTB stimulates immune system by inducing maturation of APC (8). Furthermore, rCTB would work as a carrier molecule for APC to deliver extracellular antigens, because strong binding of pentameric rCTB to GM 1 gangliosides would enhance antigen uptake by DC (8).…”
Section: Discussionmentioning
confidence: 99%
“…Like other bacterial components, rCTB stimulates immune system by inducing maturation of APC (8). Furthermore, rCTB would work as a carrier molecule for APC to deliver extracellular antigens, because strong binding of pentameric rCTB to GM 1 gangliosides would enhance antigen uptake by DC (8).…”
Section: Discussionmentioning
confidence: 99%
“…28,29 In addition, inoculation with autoantigens was shown to generate partial diabetes suppression in patients. [30][31][32] Mucosal delivery of the cholera toxin B subunit (CTB) stimulated dendritic cell-mediated induction of IL-4 secretion by T cells and exerted a variety of distinct anti-inflammatory effects resulting in immunological suppression. [33][34][35] Oral delivery of CTB conjugated with specific autoantigens demonstrated protection of mice against several Th1 cell-mediated autoimmune diseases, including autoimmune encephalomyelitis, 36,37 autoimmune chondritis, 38 and uveitis.…”
Section: Introductionmentioning
confidence: 99%